Factors affecting students' learning strategies at school - Yaacob, Aizan; Shapii, Aspalila bt.; Saad, Alobaisy Ayman; Al-Rahmi, Waleed Mugahed; Al-Dheleai, Yahya M.; Yahaya, Nor-affandy; Al-Maatouk, Qusay (International Journal of Engineering and Technology, 2018)
English language is spoken, written, read, and understood widely in most parts of the world. The significance of English language today underlines the significance of its vocabulary learning strategies. The aim of this study is, therefore, to examine factors affecting vocabulary learning strategies (VLS) among Saudi students studying Saudi School in Malaysia (SSM). To achieve the objective of the paper, two dif-ferent tools of data collection have been adopted by the researcher. The study employs both semi-structured interview, where a total of seven students participated, as well as class observation which complement the findings of the interview. The study generated three themes from the interviews as the factors affecting vocabulary learning of students: language learning environment, attitude and beliefs, and Motivation. The findings of the study show that vocabulary-learning strategies (VLS) in SSM is affected by three major factors: language learning envi-ronment, attitude and beliefs of students, and motivation.